1983
DOI: 10.1111/j.1365-2222.1983.tb02589.x
|View full text |Cite
|
Sign up to set email alerts
|

The late bronchus‐obstructive response to bronchial challenge with pigeon faeces and its correlation with precipitating antibodies (IgG) in the serum of patients having long‐term contact with pigeons

Abstract: SummaryFrom a total of 160 patients with allergic bronchial asthma or chronic asthmatic bronchitis, eighteen (11.3%) patients reported being regularly exposed to pigeons. In these eighteen patients, bronchial provocation tests with pigeon faeces were performed and the precipitating antibodies (IgG) in their serum against pigeon faeces and serum were estimated. Of the eighteen patients, seven (39%) demonstrated a ‘late bronchus‐obstructive response’ to pigeon faeces. Three patients developed only an ‘isolated l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Diagnosis is based on characteristic clinical symptoms and demonstration of antigen-specific IgGs (1)(2)(3)(4). Antigen exposure also elicits production of IgGs in other pulmonary diseases, such as invasive aspergillosis (5,6 ), allergic bronchopulmonary aspergillosis (ABPA) 3 (7 ), and ABPA in cystic fibrosis (8 ).…”
mentioning
confidence: 99%
“…Diagnosis is based on characteristic clinical symptoms and demonstration of antigen-specific IgGs (1)(2)(3)(4). Antigen exposure also elicits production of IgGs in other pulmonary diseases, such as invasive aspergillosis (5,6 ), allergic bronchopulmonary aspergillosis (ABPA) 3 (7 ), and ABPA in cystic fibrosis (8 ).…”
mentioning
confidence: 99%
“…We found the late broncho-obstructive response to bronchial challenge with pigeon dropping antigen in 31 % of exposed individuals (breeders, their family members, neighbours) (24). The study showed that the positive precipitating antibodies in the serum of individuals exposed to pigeon droppings are an important diagnostic parameter for PBD.…”
Section: L)mentioning
confidence: 77%
“…and neighbours (24), all of whom having been directly or indirectly exposed to pigeon droppings. The eight patients who did not alter their contact with pigeons reported persisting nasal complaints despite therapy.…”
Section: L)mentioning
confidence: 99%
See 2 more Smart Citations